The Amazonian kambô frog Phyllomedusa bicolor (Amphibia: Phyllomedusidae): Current knowledge on biology, phylogeography, toxinology, ethnopharmacology and medical aspects - Thais A. C. Nogueira; Thais A. C. Nogueira; Igor Luis Kaefer; Marco A. Sartim; Marco A. Sartim; Marco A. Sartim; Manuela B. Pucca; Jacqueline Sachett; Jacqueline Sachett; Jacqueline Sachett; André L. Barros; Moysés B. A. Júnior; et al. (Frontiers Media S.A., 2022)
Phyllomedusa bicolor (Phyllomedusidae), popularly known as the kambô in Brazil, is a tree frog that is widely distributed in South American countries and is known for producing a skin secretion that is rich in bioactive peptides, which are often used in indigenous rituals. The biological effects of the skin secretion were observed in the first studies with indigenous communities. Over the last six decades, researchers have been studying the chemical composition in detail, as well as the potential pharmacological applications of its constituents. For this reason, indigenous communities and health agents fear the misuse of the kambô, or the inappropriate use of the species, which can result in health complications or even death of users. This article seeks to provide a transdisciplinary review that integrates knowledge regarding the biology of P. bicolor, ethnoknowledge about the ritual of the kambô, and the chemistry and pharmacology of the skin secretion of this species, in addition to medical aspects of the indiscriminate use of the kambô. Furthermore, this review seeks to shed light on perspectives on the future of research related to the kambô.